Towards a buoyant political ecology: Rethinking marginalization for coastal climate change adaptation in the tropics - Haripriya Rangan; Judith Carney (Journal of Political Ecology)
The land-water dichotomy plays a key role in the prevailing global climate change adaptation (CCA) policy discourse for tropical coastal areas. This dichotomy is implicitly informed by a land centered conception of property which regards areas that fluctuate between water and land, or 'aquaterras', as marginal and in need of development to make them economically profitable. By adopting this perspective, mainstream CCA policies ignore the diverse, vernacular systems of adaptation that communities that dwell in such tropical coastal aquaterras have developed through multigenerational and lived experiences to negotiate climatic and contingent uncertainties. The article calls on political ecologists to jettison land-centered, economic representations of marginality and marginalization in favor of a 'buoyant', critical CCA approach which recognizes and builds on the vernacular knowings and expertise of tropical coastal aquaterra communities.